Assessing irrigation-induced selenium and iron in the stream-aquifer system of the Lower Arkansas River Valley, Colorado - Donnelly, Joseph P., author; Gates, Timothy K., author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
Water quality data on Se and Fe have been collected since April 2003 in a study of the lower Arkansas River valley, Colorado. Data were obtained from 19 surface water locations and from 50 ground water monitoring wells using low-flow sampling techniques. GIS mapping and statistical analysis were used to characterize the occurrence, severity, and spatial and temporal distribution of Se and Fe in the study area. Results indicate dissolved Se concentrations ranging from about 0 to 3560 μg/L with a median of about 16 μg/L in the ground water, including two significant hot spots. River concentrations range from 5.4 to 23 μg/L, often exceeding stream standards. Dissolved Fe concentrations in the wells range from about 0 to 1560 μg/L, however only about twenty percent of the samples were above the analytical detection limit. Relationships were explored between Se concentrations and more-easily monitored indicators such as electrical conductivity and sulfate concentration. Statistically significant non-linear relationships exist between Se and these constituents and will be tested for predictive capability.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.